Career motivation of 1st year nursing and midwifery students: A cross-sectional study - Wareing, Dr Mark; Newberry-Baker, Ria; Sharples, Dr Adrienne; Pye, Sarah (International Journal of Practice-based Learning in Health and Social Care, 2024)
This paper presents findings from a cross-sectional study into the motivational factors of students who chose nursing and midwifery as a career. 189 students from the University of Bedfordshire (UoB) and 223 students from Canterbury Christ Church University (CCCU) completed a questionnaire at the start of their studies in 2018. The findings are generated from the first stage of the Placement, Impact, Experience and Destination (PIED) study into student belongingness on placement and the influence of practice on the first career destination of newly qualified nurses and midwives. An in-class questionnaire was administered to 1st year pre-registration adult, child and mental health nursing and midwifery students to identify the intrinsic and extrinsic factors that influenced their motivation to choose nursing or midwifery as a career. A mix methods study design was adopted for the PIED study where participants completed a survey that collected quantitative and qualitative data and administered during the course induction period. Motivation scores were found to be high in both cohorts, with students at both sites endorsing intrinsic motivational factors over extrinsic at statistically significant levels. The strongest intrinsic factors appeared to be a desire to help and care for people and play a useful role in society, whereas the strongest extrinsic factors were career stability and the ability to work in different regions and countries. The study suggests that the influence of family and friends continues to exert a strong intrinsic motivational influence on the career choices of students, particularly those under the age of 25. Identifying the motivational factors of first year nursing and midwifery students presents employers with an opportunity to tailor strategies to recruit apprentices, enable placement partners to enculturate prospective employees into the workforce and understand the relationship between extrinsic factors and practice learning to successfully recruit graduates.